Analisis pendapatan dan penyerapan tenaga kerja pada usaha mikro kecil dan menengah sebelum dan setelah pandemi covid-19 (studi kasus pada warung bakso di Kecamatan Alam Barajo Kota Jambi) - Agu Sujana; Zamzami, Zamzami; Kusuma Edy, Jaya (e-Journal Perdagangan Industri dan Moneter, 2023)
This study aims to (1) To find out and analyze the characteristics of UMKM Warung Bakso actors in Alam Barajo District (2) To find out and analyze the income of Bakso stalls in Alam Barajo District, Jambi City before and after the Covid-19 pandemic (3) To find out and analyze absorption of Bakso stalls in Alam Barajo District, Jambi City before and after the Covid-19 pandemic (4) To find out and analyze differences in income and employment of MSME meatball stalls in Alam Barajo District before and after the Covid-19 pandemic. The analytical method used in this study was descriptive analysis and quantitative analysis. The results of the research on the income of respondents who experienced income after Covid-19 were 10 (90.9%) more respondents than respondents who experienced a decrease in income by 1 (9.1%) respondents. Several respondents experienced an increase in the number of workers after Covid-19 by 6 (54.5%) more respondents than the number of respondents who experienced a decrease in the number of workers by 5 (45.5%). There is a significant difference between the income of UMKM Warung Bakso in Alam Barajo District before and after the Covid-19 pandemic and there is no difference between the number of MSME Warung Bakso workers in Alam Barajo District before and after the Covid-19 pandemic.